DEVELOPMENT OF PHYSICAL QUALITIES AND ITS INFLUENCE ON GYMNASTIC EXERCISE TECHNIQUE (American Journal of Pedagogical and Educational Research, 2023)
Technical training of gymnasts is based on their physical qualities. If the gymnast's physical ability does not meet the requirements of the gymnastic element technique, it will not be possible to perform any exercise correctly. In addition, it is necessary to ensure the formation of high quality of strength training exercises from the point of view of improving technical skills. In this regard, special training for gymnasts is important. Especially during the competition, it is important for gymnasts to form qualities specific to the studied elements. Therefore, it is necessary that the process of teaching movement skills in each specific situation has its own characteristics.